Greenhouse Gas Mitigation Costs of Reduced Nitrogen Fertilizer - Andreas Meyer-Aurich; Yusuf Nadi Karatay (Agriculture, 2022)
The reduction of nitrogen (N) fertilizer use is a possible greenhouse gas (GHG) mitigation option, whereas cost estimation highly depends on assumptions of the yield response function. This paper analyzes the potential and range of GHG mitigation costs with reduced N fertilizer application based on empirical yield response data for winter rye (Secale cereale L.) and rapeseed (Brassica napus L.) from field experiments from 2013 to 2020 in Brandenburg, Germany. The field experiments included four to five N rates as mineral fertilizer treatments. Three different functional forms (linear-plateau, quadratic, and quadratic-plateau) were estimated to model yield response as a function of N supply. Economic calculations were based on relevant price–cost ratios. The results indicate that the opportunity costs of applying less fertilizer and the resulting GHG mitigation thereof vary in a great range across the years and crops estimated by different yield response functions. The linear-plateau function predominantly results in lower GHG mitigation costs than the quadratic and the quadratic-plateau function. On average, over eight years, a moderate reduction of N fertilizer (up to 20 kg/ha) offers a cost-efficient option for mitigating GHG emissions below EUR 50 per ton of CO2eq, even resulting in net profit gain in some cases.